A dictionary of nonprofit terms and concepts - Smith, David Horton (Philanthropic and nonprofit studies., 2006)
This reference work defines more than 1,200 terms and concepts that have been found useful in past research and theory on the nonprofit sector. The entries reflect the importance of associations, volunteer administration, leisure, and political activities of nonprofits.